2012
DOI: 10.1080/19440049.2012.694121
|View full text |Cite
|
Sign up to set email alerts
|

Polycyclic aromatic hydrocarbons in animal-based foods from Shanghai: bioaccessibility and dietary exposure

Abstract: A total of 175 samples of 18 types of food were collected from markets in Shanghai, China, and the concentrations and bioaccessibility of 15 priority-controlled polycyclic aromatic hydrocarbons (PAHs) in these samples were determined. The mean concentrations of PAHs varied between 2.4 and 47.1 ng g(-1) wet weight, with the highest being observed in snail and lowest in chicken. The concentrations were lower than the maximum levels of PAH allowed for food per EU regulations. Among the PAHs measured, phenanthrene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(29 citation statements)
references
References 23 publications
3
25
0
1
Order By: Relevance
“…This result was comparable to previous investigations, which found that tissue residues of organic chlorine pesticide in fish did not correlate with lipid levels (Fisher, 1995). Yu et al (2012) also found that in most of investigated seawater fish samples, lipid was not correlated with the concentrations of PAHs. The observation in Fig.…”
Section: Introductionsupporting
confidence: 90%
“…This result was comparable to previous investigations, which found that tissue residues of organic chlorine pesticide in fish did not correlate with lipid levels (Fisher, 1995). Yu et al (2012) also found that in most of investigated seawater fish samples, lipid was not correlated with the concentrations of PAHs. The observation in Fig.…”
Section: Introductionsupporting
confidence: 90%
“…5 g/day obtained from the survey conducted by Wang et al (Wang et al 2005). The most four consumed seafood species by Xiamen residents are fish (16.1 (2.14, 42.9) g/day), mollusk (12.9 (3.21, 34.3) g/day), alga (9.29 (2.14, 19.3) g/day), and crustacean (4.29 (1.34, 12.0) g/day), which is lower than fish (40.8 g/day) in Shanghai (Yu et al 2012) and fish (71.43-107. 14 g/day) in Lake Phewa, Nepal (Thapa et al 2014).…”
Section: Seafood Consumption Of the Participantsmentioning
confidence: 85%
“…In that study, fish sold in five large Chinese cities were analyzed, and the contaminant concentrations were found generally to be lower in farmed fish than in wild fish. The concentrations of a number of pollutants in different animal-based foods from Shanghai have also been determined in a number of studies (Yu et al, 2011(Yu et al, , 2012bLei et al, 2013), but the health risks posed to Shanghai residents by contaminants in foods containing fish products have been evaluated in only one study (Lei et al, 2015). In that study, the estimated total daily intake of contaminants in aquatic products (fish and shellfish) was found to be much higher than the estimated total daily contaminant intake in livestock and poultry products (Lei et al, 2015).…”
Section: Introductionmentioning
confidence: 96%